Bilateral vulval emphysema: A rare complication of laparoscopic hysterectomy (Indian Journal of Case Reports, 2025)
Vulvar edema can present in various obstetric and gynecological conditions in a patient. There are instances of it presenting after tocolysis of pre-term labor, secondary to ovarian hyperstimulation syndrome, as a complication of severe pre-eclampsia; however, vulvar edema presenting after laparoscopy or intra-operatively during laparoscopy is rarely reported. A 44-year-old patient, P5L5 with a previous 1 lower segment cesarean section and 4 vaginal birth after cesarean presented with abnormal uterine bleeding due to leiomyoma, for the past 8 months, which was not responding to medication. A total laparoscopic hysterectomy was planned. On cauterizing and cutting off bilateral round ligaments, a bilateral swelling was noted over both the labia Majora, which was reducible on manual compression. It was concluded to be due to the bilateral patent canal of nuck. It may be more prevalent in asymptomatic adults than currently appreciated. Our case is the only one documented in the literature so far of a bilateral patent canal of nuck, presenting in an asymptomatic adult. Only one other similar case of a unilateral patent canal of nuck has been reported. In conclusion, vulvar edema following a laparoscopic surgery is uncommon and is usually treated conservatively. However, in our case, the vulvar edema (emphysema) was evident intra-operatively, which was bilateral, due to the patent canal of nuck, which is a very uncommon presentation and difficult to diagnose pre-operatively, especially in adults who doesn’t present with any signs till adulthood.